Part Four: The Research Dissertation: Planning, Producing and Writing a Thesis. Issue 11 (November 2015) - Quick, J; Hall, S
Dissertations have become common inclusions to postgraduate degrees in healthcare. To the novice researcher, undertaking an extensive project of this kind can appear daunting. In this final article in the series ' Spotlight on Research ', Julie Quick and Susan Hall advise perioperative practitioners on how to plan, produce and write a research dissertation. Guidance is also given on disseminating the results from research studies.